Standarisasi Simplisia Kering Daun Beluntas (Pluchea indica L.) dari Tiga Daerah Berbeda - Talia, Sela; Wijaya, Sumi; Setiawan, Henry Kurnia (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2017)
Indian Fleabane (Pluchea indica L.) are commonly used as hedgerows and traditionally the leaves are used as fresh salad or medicines to eliminate body odor, febrifuge, cough medicine, and antidiarrheal drugs. Along with the increasing technology of natural materials and the tendency of people to use products derived from natural materials, especially medicinal plants, a reference which contains the requirements for the quality of natural ingredients that are suitable for use as medicinal ingredients is needed. This research aims to determine the profile of specific and non specific standardization of dried powder of indian fleabane leaves. Standardization of indian fleabane leaves covers specific parameters and non specific parameters, characterization of microscopic characteristics of indian fleabane (Pluchea indica L.) leaves, characterization of the content of secondary metabolites using thin layer chromatography (TLC), determination of spectrum profiles using infrared spectrophotometer (IR), and determination of the levels of secondary metabolites by spectrofotometry. The data obtained is descriptive data that reflect the acquisition of data from 3 different locations. Based on microscopic observations indian fleabane leaf dried powder has vascular bundles with spiral thickening, anomocytic stomata, and multicellular trichomes. Ethanol solubility of dried powder indian fleabane is ≥5% while water solubility in water is ≥26%. The results of phytochemical screening showed positive results on the observations of alkaloids, flavonoids, phenols, steroids and terpenes. Total ash content is